Importance of Epstein–Barr virus infection in pathogenesis of proliferative complications in children with endogenous uveitis - M. S. Petrovskaya (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Endogenous uveitis (EU) in children is a multifactorial sight-threatening disease that reduces patient’s quality of life. Proliferative syndrome (PS) coupled to developing adhesions, opacity of vitreous body, epiretinal and preretinal membranes is one of the most serious EU complications, with yet-unknown pathogenesis. Among the numerous trigger factors, a role for infections, particularly human herpes group-driven, is proposed. The goal of the study was to assess a potential role of Herpes simplex viruses type 1 (HSV-1), Herpes simplex viruses type 2 (HSV-2), Epstein–Barr virus (EBV) and Cytomegalovirus (CMV) played in the PS pathogenesis in children with endogenous uveitis. 112 patients aged 3–17 years (mean age 10 years) with (93 patients)/without PS (19 children) were examined. IgM and IgG antibodies (markers of chronic and active infection) against HSV-1/2, EBV and CMV were detected by ELISA. A significantly increased PS rate in infected vs. uninfected children was revealed solely for EBV infection (p = 0.03), but not for HSV-1/2 (p > 0.05) or CMV-positive patients (p > 0.05). However, PS emergence in EBV-negative patients also suggests that some factors might contribute to proliferation in intraocular inflammation. In addition, level of serum IL-8 and IL-6 were assessed by multiplex analysis in 28 children. It was found that IL-8 was detected in all patients, with great individual fluctuations (5.6–2743 pg/ml). Enhanced systemic IL-8 level tended to rise in patients with more prominent proliferation and serological markers of EBV reactivation. However, serum IL-6 was detected by about 2-fold less often reaching up to 55% cases (variation of individual indices 1.3–35.5 pg/ml). A correlation between PS severity, EBV infection activity and systemic IL-6 level was not observed. Further studies evaluating a role of EBV infection in PS pathogenesis pediatric endogenous uveitis are necessary, as it may underlie a rationale for including antiherpetic drugs into a combination therapy.